ANALISIS NET PROFIT MARGIN TERHADAP DIVIDEND PAYOUT RATIO (Studi kasus pada PT Gudang Garam Tbk) - Andri Helmi Munawar; Yuningsih Yuningsih (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2019)
ABSTRACT This study aims to determine and analyze the effect of Net Profit Margin on the Dividend Payout Ratio with a case study object study at PT Gudang Garam Tbk. This study uses an independent variable namely Net Profit Margin and the dependent variable, Dividend Payout Ratio. This study uses a quantitative approach with types of explanatory research. In this study the authors used a purposive sampling technique with secondary data with time series analysis at PT Gudang Garam Tbk for the period 2007-2016. The data analysis technique used by the writer is descriptive data analysis, classic assumption test with statistical techniques using simple linear regression. Based on the analysis of the Net Profit Margin variable and the Dividend Payout ratio in PT Gudang Garam Tbk for the period 2007-2016, it tends to fluctuate. The test results of the correlation coefficient of 0.335 means that the relationship between variables is in the low category, the magnitude of the coefficient of determination or the effect of Net Profit Margin on the Dividend Payout Ratio at PT Gudang Garam Tbk for the period 2007-2016 is 11.2%. The hypothesis test results state that there is no significant influence between Net Profit Margin on the Dividend Payout Ratio at PT Gudang Garam Tbk for the period 2007-2016. Keywords: Net Profit Margin, Dividend Payout Ratio.